Color stability of a composite resin modified by ZnO and TiO2 antibacterial nanoparticles - Dias, Hercules Bezerra; Sicilia, Lucca; Bernardi, Maria Ines Basso; Hernandes, Antônio Carlos; Rastelli, Alessandra Nara de Souza (Brazilian Dental Science, 2026)
Objective: To evaluate the color stability of a composite resin modified with ZnO and TiO2 nanoparticles (both pure and silver decorated), synthesized via polymeric precursor and hydrothermal methods. Material and Methods: Filtek™ Z350 XT resin was modified with 2 wt% of nanoparticles, specimens were prepared (n=180), and photoactivated. Specimens were immersed in coffee and artificial saliva; color changes were measured spectrophotometrically, converted to NBS units, and analyzed using repeated measures ANOVA (p<0.001). Results: Coffee immersion caused the greatest discoloration, with the unmodified resin reaching ΔE* = 15.48 after 90 days. Resins containing ZnO/Ag and TiO2/Ag exhibited even higher color instability (ΔE* = 23.14 and ΔE* = 18.71, respectively). Conclusion: While ZnO and TiO2 tested nanoparticles may offer antimicrobial advantages, their incorporation, particularly in silver-decorated forms, can negatively impact the color stability of composite resins exposed to chromogenic agents like coffee. KEYWORDS Coloring agents; Composite resins; Nanoparticles; Titanium; Zinc oxide.